UMA FICÇÃO QUE FRUI O FLUIR DA FÍSICA: UMA ANÁLISE DO ROMANCE SONHOS DE EINSTEIN, DO FÍSICO ALAN LIGHTMAN - Nascimento, Jeverson Machado do (2013)
The main goal of our work was to undertake a study of the novel Einstein's Dreams by Alan Lightman, in order to exploit its potential discourse regarding the meeting of the elements of the day and the night, which are corresponding, in Bachelard's beautiful metaphor, to the exercise of literary writing and the scientific activity. Therefore, the theoretical framework that guides us consists primarily of the works of Mikhail Bakhtin - particularly the philosophical theory contained in Toward a Philosophy of the Act (2010a) and his theory of aesthetics of the novel contained mainly in Questions of Literature and Aesthetics (2010b) - as well as the epistemological studies of Gaston Bachelard, especially the works The New Scientific Spirit (1988), The Philosophy of No (1991) and The poetics of reverie (1988b). Reading these authors we intended to understand concepts we consider as parallel, such as daydreaming and dreams, dialogism and philosophical epistemological plurality, dialectical pluralism; these concepts were vital so we could consider our object as a meeting between the daytime and nighttime, a discourse that walks along the horizon during dusk and dawn. Thus, we list some elements of the work that we understand as essential for the analysis, as the way the main character was built, the explicit context of the work, how the scientific and philosophical plurality of time presents itself.